Pengaruh Kegiatan Meronce Mapoli (Makaroni, Pom-Pom, Tali) terhadap Motorik Halus Anak Usia 4-5 Tahun - Dini Silvia Fernanda; Nurul Khotimah; Achmad Sya'dullah; Sri Widayati (Departement of Mathematics Education, 2024)
This study is motivated by problems in the development of children aged 4-5 years where there are problems in early childhood institutions in the aspect of children's fine motor development, namely children are less able to coordinate their hands and eyes well, therefore researchers conducted MAPOLI merging activities on the fine motor skills of children aged 4-5 years with the aim of knowing the effect of these activities on children's fine motor development, so that children's fine motor problems can be resolved. This study uses a quantitative approach with a type of Quasi Experimental research with a nonequivalent control group design. The samples used in this study in two institutions namely Dharma Wanita Kindergarten and Kemala Bhayangkari 1 Surabaya Kindergarten where each sample amounted to 10 children. Data collection techniques using observation with data analysis techniques using the Mann-Whithey U Test formula. Based on the research that has been done, it is obtained significant results where this MAPOLI tying activity can affect children's fine motor skills because the control class has 7 children who have increased while the experimental class of 10 children has an overall increase, namely children are able to coordinate their hands, able to grasp, able to grasp and complete it independently with a fairly fast time.